Hubungan pengalaman kekerasan seksual dengan kesehatan mental mahasiswa di Kota Bandung - Utomo, Shella Febrita Puteri; Yuliani, Anita; Nurfadilah, Nisa; Islah, Ajeng (JOURNAL OF Mental Health Concerns, 2024)
Background: Sexual violence against students on campus has become an important issue. The experience of sexual violence among students certainly has a direct impact on mental health and affects the academic process so that students do not receive well-being and experience prolonged trauma. Purpose: To assess the experience of sexual violence and mental health among students in the campus environment. Method: A descriptive quantitative cross sectional approach, the population in this study were all students using a convenience sampling technique so that data was obtained as many as 216 respondents. The instrument uses the SDQ-20. Data analysis used the chi-square test. Results: A relationship between the experience of sexual violence and mental health status with a sig value showing a P value of 0.000. Conslusion: The experience of incidents of sexual violence has become a mental health problem with complaints, anxiety, somatic and depression. This research can be input for policy makers in education to design further more effective prevention and support programs in the campus environment. Keywords: Mental Health; Students Experience; Sexual Violence. Pendahuluan: Kekerasan seksual pada mahasiswa di lingkungan kampus sudah menjadi isu yang penting. Pengalaman dari kekerasan seksual pada mahasiswa tentu berdampak langsung pada kesehatan mental dan mempengaruhi proses akademik sehingga mahasiswa tidak mendapatkan kesejahteraan serta mengalami trauma berkepanjangan. Tujuan: Untuk menilai adanya hubungan pengalaman kekerasan seksual dengan kesehatan mental pada mahasiswa. Metode: Deskriptif kuantitatif pendekatan cross sectional, populasi pada penelitian ini seluruh mahasiswa dengan teknik convenience sampling sehingga di dapatkan data sebanyak 216 responden. Instrumen menggunakan SDQ-20. Analisa data menggunakan uji chi -square. Hasil: Adanya hubungan antara pengalaman kekerasan seksual dengan status mengalami kesehatan mental dengan nilai sig menunjukan P Value 0,000. Simpulan: Pengalaman atas kejadian kekerasan seksual menjadi masalah kesehatan mental dengan keluhan, cemas, somatik, dan depresi. Penelitian ini dapat menjadi masukan bagi pengambil kebijakan di pendidikan untuk merancang program pencegahan dan dukungan lebih lanjut yang lebih efektif di lingkungan kampus. Kata-kata kunci: Kesehatan Mental, Mahasiswa Pengalaman Kekerasan Seksual.